Development and validation of a vero cell-based suspension method for the detection of Zika virus - Dina Popuche; Alfredo Huaman; Steev Loyola; María Silva; Sarah A. Jenkins; Carolina Guevara (Revista Peruana de Medicina Experimental y Salud Pública, 2023)
Objective. To develop and validate a cell suspension method using Vero 76 cells for culturing Zika virus (ZIKV) based on infection of detached freshly seeded cells.  Material and methods. Three different multiplicities of ZIKV infection were used to develop and compare this novel method to the standard confluent cell monolayer method. In addition, we preliminary validated the cell suspension method using well-characterized ZIKV positive and negative clinical samples. The standard confluent cell monolayer method was used as the reference method, and viral isolation was confirmed by a ZIKV-specific RT-PCR. We estimated the sensitivity, and its 95% confidence intervals, for the cell suspension method. Also, a technical comparison of the cell suspension method against the cell monolayer method was performed. Results. Our findings suggest that both the viral load and replication of ZIKV were comparable between both monolayer- and suspension-infection methods. Although both methods were suitable for culturing and isolating ZIKV, the cell suspension method was easier, cheaper, and quicker as well as a sensitive isolation technique. The cell suspension method was significantly more sensitive in detecting Zika in inconclusive cases by RT-PCR, with a fourfold increase compared to the confluent cell monolayer method. Conclusion. The cell suspension method has the potential to be an effective method for cultivating and isolating ZIKV and its application is potentially useful in both research and clinical settings.